2013
DOI: 10.5172/conu.2013.46.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Reframing spaces by building relationships: Community collaborative participatory action research with Aboriginal mothers in prison

Abstract: Aboriginal women are vastly over-represented in the Australian prison system. Their recidivism rates are high. Aboriginal women in contact with the criminal justice system also have higher rates of mental health disorders and are likely to have been a victim of violence. The majority of these women are mothers. Their increasing incarceration therefore has serious implications for the health and social and emotional wellbeing of their Aboriginal children, families and communities. Illustrating and exploring thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…Qualitative interviews were also conducted in WA, but followed a different methodological approach on the guidance of the WA project advisory group (PAG) (Wilson et al, 2017; Wilson, Jones, & Gilles, 2014). In acknowledgment of the heterogeneity of Aboriginal communities and experiences of colonization across Australia, the larger project was designed to be responsive to the advice of local Aboriginal researchers and community experts regarding the methods of data collection and analysis in each state (this is discussed in detail in the “Method” section) (Sherwood & Kendall, 2013). Privileging the voices, knowledge, and paradigms of Aboriginal people is a foundational principle guiding health research with Aboriginal communities (Rigney, 1999; Rynne & Cassematis, 2015; Sherwood & Kendall, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative interviews were also conducted in WA, but followed a different methodological approach on the guidance of the WA project advisory group (PAG) (Wilson et al, 2017; Wilson, Jones, & Gilles, 2014). In acknowledgment of the heterogeneity of Aboriginal communities and experiences of colonization across Australia, the larger project was designed to be responsive to the advice of local Aboriginal researchers and community experts regarding the methods of data collection and analysis in each state (this is discussed in detail in the “Method” section) (Sherwood & Kendall, 2013). Privileging the voices, knowledge, and paradigms of Aboriginal people is a foundational principle guiding health research with Aboriginal communities (Rigney, 1999; Rynne & Cassematis, 2015; Sherwood & Kendall, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The few examples of PAR in prisons have reported mixed success in using PAR to create positive change and empower participants (e.g. Bennett, Perry, & Lapworth, 2010; Drake, 2014; Fine and Torre, 2006; Martin et al., 2013; Martin, Murphy, Chan, et al., 2009; Martin, Murphy, Hanson, et al., 2009; Sherwood & Kendall, 2013; Sullivan, Hassal, & Rowlands, 2008; Walsh, Forsyth, Senior, O’Hara, & Shaw, 2014; Ward, Bailey, & Boyd, 2012). For example, Drake (2014) used action research-inspired approaches to gain prisoners’ perspectives on the realities of being imprisoned, creatively collaborating with correctional officers to gather the data.…”
mentioning
confidence: 99%
“…[36] Aboriginal women are also at higher risk of mental health issues and more likely to have been victims of violence. [37] The relationship between prior history of childhood physical and sexual abuse and mental health illness equally applies here as identified earlier. It has been suggested that a major factor impacting on Aboriginal women's mental health is stress and anxiety attributed to family and children whilst incarcerated.…”
Section: Indigenous Healthmentioning
confidence: 86%